Cultural and Pragmastylistic Factors Influencing Translating Surat An-Nās of the Glorious Qura'an into English - Ali Mahmoud (My University, 2008)
The study aims at discussing how cultural and pragmastylistic factors influence translating Surat An-Nās of The Glorious Qur`an into English. Four different translations are taken as a sample for the study. The paper seeks to show how these aspects constitute the main source of translation difficulties between Arabic and English. Certain linguistic terms and communicative values are culture-specific and provide an important source of religious knowledge to the source text (ST). The author tries to show how these culture-specific features are independent and unsuitable for crosscultural comparison because they are characteristics of the ST which reflect salient features of the culture associated with Arabic. He then suggests certain methods to solve these culture-bound problems when translated into the target text (T T). Finally, this paper attempts to pinpoint the relationship between pragmatic coherence and stylistic variations on the level of the ST, and how these influence its translation. The author also suggests that a systematic analysis and thorough knowledge of Qur`anic meanings are required by the translator to avoid pitfalls in translating such a text.
تأثير العناصر الثقافية والبراغماتية الأسلوبية في ترجمة سورة الناس من القرآن الكريم إلى اللغة الإنجليزية